2019
DOI: 10.4114/intartif.vol22iss64pp63-84
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Probability Estimation Decision Tree Postprocessing Method for Mining Optimal Profitable Knowledge for Enterprises with Multi-Class Customers

Abstract: Enterprises often classify their customers based on the degree of profitability in decreasing order like C1, C2, ..., Cn. Generally, customers representing class Cn are zero profitable since they migrate to the competitor. They are called as attritors (or churners) and are the prime reason for the huge losses of the enterprises. Nevertheless, customers of other intermediary classes are reluctant and offer an insignificant amount of profits in different degrees and lead to uncertainty. Various data mining model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Table 7 to find the next node in the DT. From the results in Table 7 it can be observed that when i = 1 the ANDing resulted in True and the entry at LT [3][1] is accessed and the class label yes, which is represented by L5, is returned.…”
Section: Proposed Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Table 7 to find the next node in the DT. From the results in Table 7 it can be observed that when i = 1 the ANDing resulted in True and the entry at LT [3][1] is accessed and the class label yes, which is represented by L5, is returned.…”
Section: Proposed Schemementioning
confidence: 99%
“…When the user needs a simple and interpretable classifier, DT is the most preferable one. For the automatic extraction of actionable knowledge, many researchers have considered the DT as the model [3,4,5]. In general, classification through DTs comprises three phases namely, training phase, testing phase, and classification phase.…”
Section: Introductionmentioning
confidence: 99%
“…Source : DELOITTE 2017 FROM: "Artificial Intelligence for the real word " by Thomas H Davenport and Rajeev Ronanki Furthermore, Waheed, Arshad and Kashif (2011) described effects of knowledge management practices on organizational performance, Anwar and Ba (2010) described the role of information management for the preservation of indigenous knowledge in organizations. [16,17,18] .The ultimate goal of the enterprises [19,20] is to improve their profits. Naga Muneiah, J.…”
Section: Figure )2( Percentage Of Executives Who Cite the Benefits Of Aimentioning
confidence: 99%